What Do We Know About Investment Under Uncertainty? - Alan Carruth; Andy Dickerson; Andrew Henley (University of Kent, Department of Economics, 1998)
Recent theoretical developments relating to investment under uncertainty have highlighted the importance of irreversibility for the timing of investment expenditures and their expected returns. This has subsequently stimulated a growing empirical literature which examines uncertainty and threshold effects of investment behaviour. This paper presents a review of this literature. A variety of methods have been used to investigate the empirical implication of irreversibility in investment, the majority focusing on the relationship between investment flows and proxy measures of uncertainty. A general conclusion is that increased uncertainty, at both aggregate and disaggregate levels, leads to lower investment rates. This suggests that there is an irreversibility effect, under which greater uncertainty raises the value of the "option" to delay a commitment to investment. This effect appears to dominate any positive impact on investment arising from the fact that greater uncertainty, under certain circumstances, increases the marginal profitability of capital. The methods used raise a number of issues which call into question the reliability of the findings, and these are addressed in the paper. However, if such irreversibility effects are present, then their omission from traditional investment models casts doubt on the efficacy of such specifications.
Keywords: D81; D92; E22; 330; Investment; Uncertainty; Irreversibility; Investition; Risiko; Theorie